2019
DOI: 10.1016/j.heliyon.2019.e01518
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of eco-friendly micellar-HPLC and HPTLC-densitometry methods for the simultaneous determination of paritaprevir, ritonavir and ombitasvir in pharmaceutical dosage forms

Abstract: Ombitasvir, ritonavir and paritaprevir are three recently discovered directly acting antiviral drugs (DAADs) used in combined single dose tablet dosage form for treatment of hepatitis-C viral infections (HCV). The methods of analysis followed by quality control and research laboratories are required to be economic and fast; however, these methods can also produce huge amounts of chemical waste. In this study two fast, economic and green HPLC and HPTLC methods were validated for the simultaneous determination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…The proposed method was compared to reported HPLC method 12 and UHPLC method 14 using GAPI. Figure 5 shows the GAPI pictograms for the three methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed method was compared to reported HPLC method 12 and UHPLC method 14 using GAPI. Figure 5 shows the GAPI pictograms for the three methods.…”
Section: Resultsmentioning
confidence: 99%
“…Literature review revealed that few methods were reported for the simultaneous determination of OMB, PAR, and RIT, all based on chromatographic analysis techniques. Eight papers described High Performance Liquid Chromatography (HPLC) methods using isocratic mobile phase 6–13 and two Ultra‐High Performance Liquid Chromatography (UHPLC) methodologies were reported utilizing MS/MS detection 14,15 . No UV spectroscopic methods were reported for the simultaneous determination of the three antiviral drugs under study.…”
Section: Introductionmentioning
confidence: 99%
“…Several metrics are being used for evaluation of analytical procedures. The first introduced metric was the National Environmental Methods Index (NEMI) [14]. The analytical eco-scale reported in 2012 [23] calculates penalty points for any step in the analytical procedure that doesn't match green chemistry ideas.…”
Section: Evaluation Of the Analytical Proceduresmentioning
confidence: 99%
“…Most of these are chromatographic methods focusing on identification of the drugs under study together with other diuretics and CNS stimulants in urine for purpose of doping control using ultra-high performance liquid chromatography (UHPLC) with MS/MS detection [6][7][8] or high performance liquid chromatography (HPLC) coupled with MS/MS detector [9][10][11][12][13]. Such reported methods are expensive due to the high cost of mass detectors especially when coupled with UHPLC due to the added working and maintenance cost and hence not favored by users in pharmaceutical economic facilities who require more simple and cheap methodologies for the analysis purposes [14]. Other methods were reported using HPLC with UV/VIS detection [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Each sample was filtered and the amount of cefixime dissolved was determined using a UV Spectrophotometer at a wavelength of 287nm. [14][15][16] Antimicrobial studies…”
Section: Zeta Potentialmentioning
confidence: 99%